QOLBUN SALIM DALAM AL-QUR’AN (Kajian tafsir muqorin perspektif tafsir al-Kabir/Mafatih al-Ghaib dan Tafsir al-Mishbah) - Achmad Syarwani Abdan; Miftara Ainul Mufid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the concept of Qolbun Salim in the Qur’an through a comparative tafsir (muqāran) analysis between Tafsir al-Kabir/Mafatih al-Ghaib by Fakhruddin al-Razi and Tafsir al-Mishbah by M. Quraish Shihab. The research adopts a qualitative approach using library research, focusing on primary sources such as the Qur’an and the two tafsir works, as well as secondary sources including books, scholarly articles, and related Islamic literature. The analysis compares relevant Qur’anic verses, hadith, and scholars’ interpretations to identify similarities and differences. The findings reveal that Fakhruddin al-Razi defines Qolbun Salim as a heart free from spiritual diseases, polytheism, and hypocrisy, fully devoted to Allah. Quraish Shihab interprets it as a heart safe from moral and spiritual corruption, characterized by sincerity, tranquility, and obedience to Allah. Both agree that Qolbun Salim is a prerequisite for salvation in the Hereafter, but they differ in emphasizing theological versus psychological aspects. In conclusion, this study highlights the importance of heart purification in enhancing a Muslim’s spiritual and moral quality.